Reduced mate availability leads to evolution of self-fertilization and purging of inbreeding depression in a hermaphrodite. (1st March 2016) - Noël, Elsa; Chemtob, Yohann; Janicke, Tim; Sarda, Violette; Pélissié, Benjamin; Jarne, Philippe; David, Patrice
Abstract: Basic models of mating-system evolution predict that hermaphroditic organisms should mostly either cross-fertilize, or self-fertilize, due to self-reinforcing coevolution of inbreeding depression and outcrossing rates. However transitions between mating systems occur. A plausible scenario for such transitions assumes that a decrease in pollinator or mate availability temporarily constrains outcrossing populations to self-fertilize as a reproductive assurance strategy. This should trigger a purge of inbreeding depression, which in turn encourages individuals to self-fertilize more often and finally to reduce male allocation. We tested the predictions of this scenario using the freshwater snail Physa acuta, a self-compatible hermaphrodite that preferentially outcrosses and exhibits high inbreeding depression in natural populations. From an outbred population, we built two types of experimental evolution lines, controls (outcrossing every generation) and constrained lines (in which mates were often unavailable, forcing individuals to self-fertilize). After ca. 20 generations, individuals from constrained lines initiated self-fertilization earlier in life and had purged most of their inbreeding depression compared to controls. However, their male allocation remained unchanged. Our study suggests that the mating system can rapidly evolve as a response to reduced mating opportunities, supporting the reproductive assurance scenario of transitions from outcrossing to selfing.